no, i'm sorry

i meant a+sqrt(b) !=0 and prove a-sqrt(b)!=0, where sqrt stands for square root and != for does not equal

i'm sorry for my terminology, but i'm not used to the english one

- Sun Sep 22, 2013 4:49 pm
- Forum: Advanced Algebra ("pre-calculus")
- Topic: rational numbers
- Replies:
**3** - Views:
**1914**

no, i'm sorry

i meant a+sqrt(b) !=0 and prove a-sqrt(b)!=0, where sqrt stands for square root and != for does not equal

i'm sorry for my terminology, but i'm not used to the english one

i meant a+sqrt(b) !=0 and prove a-sqrt(b)!=0, where sqrt stands for square root and != for does not equal

i'm sorry for my terminology, but i'm not used to the english one

- Sat Sep 21, 2013 5:12 pm
- Forum: Advanced Algebra ("pre-calculus")
- Topic: rational numbers
- Replies:
**3** - Views:
**1914**

Hello and sorry if I'm not posting in the right section, but I have the following problem:

If a and b are rational numbers and sqrt from a+b does Not equal 0, how do I demonstrate that sqrt from a-b does not equal 0?

If a and b are rational numbers and sqrt from a+b does Not equal 0, how do I demonstrate that sqrt from a-b does not equal 0?